THE RELATIONSHIP BETWEEN SELF-MANAGEMENT AND QUALITY OF LIFE AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS - Ninik Ambar Sari; Ceria Nurhayati (Nurse and Health: Jurnal Keperawatan, 2021)
Background: Diabetes Mellitus (DM) is a metabolic disease characterized by high blood glucose levels as a result of insufficient insulin secretion, impaired insulin activity or both. Patients with diabetes mellitus are at risk for complications that can affect their quality of life. These complications can be minimized through self-management. Objectives: The aim of this study was to determine the relationship between self-management and quality of life in type 2 DM patients. Design: This study was a quantitative research. The design in this study was a cross-sectional analytic with a sample of 75 people who were carried out at the endocrine polyclinic RS Pusat TNI Angkatan Laut (RSPAL) DR. Ramelan Surabaya. Research instrument used the Diabetes Self-Management Questionnaire (DSMQ) developed by Schmitt et al (2013) to determine the self-management of type 2 DM patients and to measure the quality of life using the Diabetes Quality of Life Brief (DQoL Brief) instrument developed by Burrough et al (2008). The sample siza with simple random sampling method, and data analysis using spearman rank test. Results: The results showed that there was a significant relationship between self-management and quality of life in type 2 DM patients (p-value = .000, r = .394). Conclusion: There is a significant positive relationship between the level of self-management and quality of life in type 2 DM patients. From the results of the Spearman test correlation coefficient, there is a positive sign. This means that the higher the patient's self-management, it will also improve the quality of their life. The implication of this study are nurses can increase patient knowledge by providing education that focuses on improving self-management and facilitating the provision of family support as well as supervision and monitoring related to self-management by type 2 DM patients.